How do you solve #2m - 3n = 6# and #m = 3 - 2n# using substitution?

1 Answer
Mar 15, 2016

Answer:

The solution for the system of equations is:
#color(blue)(n=0#
#color(blue)(m=3 #

Explanation:

# 2m−3n=6# ..............equation #(1)#
#color(green)( m=3−2n )#.................equation #(2)#

Substituting equation #2 # in #1#:

#2m−3n=6#

#2 * color(green)( (3−2n ))−3n=6#

#6 -4n−3n=6#

#6 -7n=6#

#6 - 6 = 7n#

# 7n=0#

# n=0/7#

#color(blue)(n=0#

finding the value of #m# by substituting the value of #n# in equation #2#:

#m=3−2n #

#m=3−2 * 0 #

#m=3- 0 #

#color(blue)(m=3 #